Uomini in armi : costruzioni etniche e violenza politica / a cura di Marco Buttino, Maria Cristina Ercolessi, Alessandro Triulzi - Buttino, MarcoErcolessi, Maria CristinaTriulzi, Alessandro (Gli Alberi ; 11)
Bibliografía: p. 213-218